Advertisement Remove all ads

Ax2 + (4a2 - 3b)X - 12 Ab = 0 - Mathematics

Advertisement Remove all ads
Advertisement Remove all ads
Advertisement Remove all ads
Sum

ax2 + (4a2 - 3b)x - 12 ab = 0

Advertisement Remove all ads

Solution

ax2 + (4a2 - 3b)x - 12 ab = 0
⇒ ax2 + 4a2x  - 3bx - 12ab = 0
⇒ ax (x + 4a) - 3b(x + 4a) = 0
⇒ (ax - 3b) (x + 4a) = 0
⇒ x = `(3b)/a or -4a` are two roots of equation.

Concept: Nature of Roots
  Is there an error in this question or solution?

APPEARS IN

ICSE Class 10 Mathematics
Chapter 6 Quadratic Equation
Exercise | Q 11
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×